Aberrant Cyclin E and Hepatocyte Growth Factor Expression, Microvascular Density, and Micro-Lymphatic Vessel Density in Esophageal Squamous Cell Carcinoma. (17th September 2019) - Xie, Bo; Wang, Yuanyuan; He, Jingkang; Ni, Zhengzheng; Chai, Damin
Cyclin E and hepatocyte growth factor (HGF) have been observed as a multifaceted factor in many cancers, and the assessment of microvascular density (MVD) and micro-lymphatic vessel density (MLVD) has been used to quantify tumor angiogenesis and lymphangiogenesis. The aim of this study was to explore the association between expression of cyclin E, HGF, MVD, and MLVD, and clinicopathologic parameters in esophageal squamous cell carcinoma (ESCC). The expression of cyclin E, HGF, MVD, and MLVD were detected using immunohistochemically anticyclin E, HGF, CD34, and lymphatic vessel endothelial hyaluronan receptor 1 in 168 surgically resected ESCC cases and 30 normal esophageal mucosal samples. The expression levels of cyclin E, HGF, MVD, and MLVD were higher compared to controls. High cyclin E and HGF expression was found more frequently in the tumors larger than 5 cm ( P < .001), with poorer differentiation ( P = .034) and higher tumor node metastasis (TNM) staging ( P = .009) compared to their counterparts. Both MVD and MLVD values were found to be higher in the tumors larger than 5 cm ( P < .001), with poorer differentiation ( P < .001) and higher TNM staging ( P < .001) compared to their counterparts. Furthermore, the expression of MVD and MLVD in both the high cyclin E and high HGF expression groups was significantly higher compared to the low cyclin E and HGF expression groups ( P < .001). This study demonstrated that high cyclin E and HGF expression is closely correlated with tumor size, tumor differentiation degree, and TNM stage in patients with ESCC. These findings proposed that cyclin E and HGF could serve as novel molecular markers for preoperational evaluation of ESCC.